The role of FKBP5 genetics and epigenetics in mediating the effects of early life adversity on emotional processing brain regions in major depressive disorder - TOZZI, LEONARDO (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2018)
Major depressive disorder (MDD) is the most widespread psychiatric illness and is characterized by loss of pleasure, depressed mood, sleep disturbances and anxiety. Recently, an inflammatory theory of MDD has emerged, which postulates that chronic dysregulation of the stress hormone axis and increased inflammation might be crucial in the pathogenesis of the disorder. MDD also shows genetic high-heritability. In particular, the gene coding for FKBP5, a glucocordicoid receptor regulator protein, could play a role in vulnerability to MDD, especially in the presence of chronic environmental stressors such as childhood maltreatment. Magnetic resonance imaging (MRI) is a safe and non-invasive technique that allows the investigation of the brain in vivo by using powerful magnetic fields. MDD patients show volume reduction, grey matter loss and altered function in regions that are crucial for emotional regulation. The aim of our project was to investigate how genetics of FKBP5 and childhood adversity might interact to explain structural and functional brain abnormalities in MDD patients. For this, we conducted studies on a database collected across two sites comprising a total of 104 MDD patients and 97 healthy controls. First of all, we investigated which changes in activation and functional coupling were associated with MDD during an MRI task involving directing attention towards and away from the valence of emotional stimuli. Secondly, we investigated whether patients carrying the high-risk allele of the rs1360780 FKBP5 functional single nucleotide polymorphism showed differential activation during our task conditions compared to patients without genetic risk. We then sought to determine if these changes were mirrored by structural modifications and tested whether these could be explained by the interaction between genetic risk and exposure to childhood trauma. Thirdly, we investigated epigenetic modifications of the FKBP5 gene in depressed patients and controls. Previous studies have hypothesised that chronic stress might functionally regulate FKBP5 by methylation of its regulatory sites. We tested whether this modification was related to childhood adversity as well as to reduced grey matter and altered function in emotional processing areas. Our results have confirmed that MDD patients show differences in activation in regions involved in emotional recognition. Functional connectivity between some of these areas was also altered, in particular in trials involving regulation of negative emotions and recognition of positive ones. Furthermore, we have shown that in patients carrying the high-risk allele of rs1360780, demethylation of the intron sites of the FKBP5 gene promoter was correlated with the amount of early life maltreatment endured. Therefore, we suggest that the presence of both genetic and environmental risk factors is able to produce lasting epigenetic changes in a gene that has a prominent role in glucocorticoid receptor regulation. Childhood maltreatment also explained structural differences in temporal lobe white matter between MDD carrying different alleles of rs1360780. In addition to this, across our studies we have identified the inferior frontal lobe as a region whose structure and function are influenced by both FKBP5 allelic status and methylation. Crucially, this area was less active during emotional recognition in MDD compared to controls and its activation was inversely correlated with depression severity. Taken together, findings across our three studies provide evidence that the gene coding for the glucocorticoid regulator FKBP5 protein is a convergence point for the interplay between genetic and environmental risk factors of MDD.
APPROVED
Keywords: fMRI; MRI; genetics; FKBP5; epigenetics; depression